Utilization Of Strategic Thinking Skills in Sustaining And Maintaining Strategies In Language Learning Process - Najah, Osman (2015)
English as a second language has been learnt by all students in Malaysia throughout their years in schools and higher institutions. The amount of years students learnt English is seen as adequate to enable them to perform the language outside classroom context and to score better grades for their English SPM (Sijil Pelajaran Malaysia), a pre requisite exam for all students before entering matriculation, pre-university or diploma. However, to dismay many are still alienated to learning this language. Hence, this paper draws on research to exploit strategies in strategic thinking skills in order to sustain and maintain learning strategies especially in the process of engaging language learning. A researcher-developed taxonomy was exercised on 61 school students preparing for their SPM exam of a local school in Rompin District, Pahang. The students were facilitated by 6 undergraduates volunteer to assist on students’ progress. A learning module was developed to engage in learning process via internet and face to face consultation when needed. Motivated Strategies Learning Questionnaire (MSLQ) adapted to current context was used to measure the learning strategies, motivation and learning awareness in the pre and post treatment to seek students’ interest and motivation in language learning. Result showed that the taxonomy had positive effect on learning performance and self regulation. Both facilitator and students also display better effort in sustaining and maintaining strategies in learning process. The MSLQ result also displayed that apart from motivation, strategies is crucial in enhancing language learning and achievement. Finally, it is hope that this paper can be a guide in improving and increasing learners’ achievement.